Determinants of adoption of Mobile Healthcare Service. (8th June 2011) - Lin, Shu-Ping
The purpose of this research is to discuss the determinants influencing users' intention of Mobile Healthcare Service (MHS) by integrating Health Belief Model, Technology Acceptance Model and innovativeness. Structural Equation Modelling is used for data analysis. The results reveal the user's attitude is most critical on their intention, followed by Perceived Usefulness, Perceived Ease-of-Use, external cues to actions, and innovativeness. This means that it is essential for medical institutions to strengthen users' attitude by advocating the system's benefits and operating convenience. This research also provides MHS industry references for designing comprehensive services and enhancing existing ones to gain competitive advantage.